2016
DOI: 10.3329/jujbs.v3i2.28287
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical attributes of water of Hakaluki Haor, Sylhet, Bangladesh

Abstract: Water quality assessment has been carried out in the Hakaluki Haor of greater Sylhet district during May, 2013 to February, 2014. Water samples were collected from 5 spots during 4 seasons and a total of 15 physico-chemical parameters were studied. Significant seasonal variation was observed in all seasons among physico-chemical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…PO 4 of the water samples ranged from 0.022 to 0.078 mg L −1 . PO 4 value was about 5.58 mg L −1 at pre-monsoon (March-May) in Hakaluki haor (Islam et al, 2014). It is apparent from the above value of water sample, that the water was suitable for fish production and other aquatic organisms at Tanguar haor wetland.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…PO 4 of the water samples ranged from 0.022 to 0.078 mg L −1 . PO 4 value was about 5.58 mg L −1 at pre-monsoon (March-May) in Hakaluki haor (Islam et al, 2014). It is apparent from the above value of water sample, that the water was suitable for fish production and other aquatic organisms at Tanguar haor wetland.…”
Section: Resultsmentioning
confidence: 84%
“…NO 3 of the water samples ranged from 0.763 to 1.769 mg L −1 . Islam et al (2014) found the average NO 3 value about 15.6 mg L −1 at Premonsoon (March-May) in Hakaluki haor. PO 4 of the water samples ranged from 0.022 to 0.078 mg L −1 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The radioactivity levels of the sample water were analyzed and the gross α and β were found to be 0.01 and 0.10 Bq/l. For Hakaluki Haor, mean water temperature 26.8°C, Secchi depth 0.43 m, TDS 68.68 mg/l, conductivity 141.42 μS/cm, pH 6.44 and DO 4.90 mg/l were reported (7) . This indicates low pH turbid water having a relatively high TDS and electrical conductivity of Hakaluki Haor.…”
Section: Resultsmentioning
confidence: 99%
“…The first hydrobiological research on Hakaluki Haor was carried out where a list of phytoplankton, benthic algae and macrophytes growing in the pelagic and littoral area of the Haor were published (6) . Physicochemical attributes of Hakaluki Haor also studied (7) . In 2017, an untimely flash flood occurred in April causing inundation of vast areas of its rice fields and an instant mortality of fishes, aquatic birds, ducks, reptiles, etc.…”
Section: Introductionmentioning
confidence: 99%